Detection of Seed Borne Fungi by conventional and modern methods - Yadav, Manoj Kumar; Aravindan, S.; Mukherjee, A. K.; Lenka, S.; Sharma, S. K. (Indian Farming, 2016)
Seed health has become an important quarantine issue, mainly inthe international movement of seeds and germplasm exchange. Thus, it is crucial to make sure that no potentially damaging pathogens are established on seeds. Conventional seed detection methods including visual examination, selective media, seedling grow-out assay and the serological assays have been usedextensively, but all have limitations like inefficiency and sensitivity. The Indian Farming May 2016 41 molecular methods have shown great potential for improving pathogen detection in seeds as it embodies many of the key characteristics including specificity, sensitivity rapidity, ease of implementation and interpretation and applicability. PCR and its modifications including BIOPCR, IMS-PCR and MCH-PCR may offer opportunities to evade inhibitory compounds while improving detection of seedborne pathogens. IMS-PCR and MCHPCR are mainly striking since they provide simple and universally applicable formats for culturable and nonculturable pathogens in seeds. Further, reduced cost and more efficiency will ultimately allow DNAbased detection methods to replace the vast range of seed detection assays presently engaged and provide advanced detection abilities essential for healthy seedling establishment.